Assembly of Fine-Pitch Package Integrated Circuits in a Laminated Transfer Process for E-Textile Applications - Yi Li; Thomas Greig; Abiodun Komolafe; Russel Torah; Steve Beeby (Engineering Proceedings)
Laminating screen-printed, flexible transfers is a reliable method of creating electronic connections across a textile. However, their limited resolution means that it is not possible to solder on fine-pitched components. An alternative substrate, etched copper on polyimide is compatible with fine pitch components, but is unsuitable for use over large areas. This work examines methods of combining the two systems to produce e-textiles that combine both their benefits. Tensiometer tests showed that 3M 9087 double-sided tape was the most robust for attaching the polyimide, and electrical interconnects formed by overlapping the transfer on top of the polyimide circuit gave the most stable and lowest resistance connections.